2014
DOI: 10.5120/16181-5397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Beam Divergence on WDM-FSO Transmission System

Abstract: This work is focused to carry out the investigation of wavelength division multiplexing (WDM) approach on free space optical (FSO) transmission systems. In this work, 8 independent channels having capacity of 1.56 Gbps each are transmitted over FSO link having a span of 15km by considering clear weather conditions. Furthermore, the performance of proposed FSO-WDM system is also evaluated on the effect of varying the beam divergence and results are reported in terms of SNR, BER and eye diagrams. KeywordsFree sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Figure 8 shows BER versus signal power at 4 km for RZ modulation format. For channels 1,4 been observed that if we increased signal power from WDM transmitter side BER is decreased. Figure 9 shows -factor versus signal power at 4 km for RZ modulation format.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure 8 shows BER versus signal power at 4 km for RZ modulation format. For channels 1,4 been observed that if we increased signal power from WDM transmitter side BER is decreased. Figure 9 shows -factor versus signal power at 4 km for RZ modulation format.…”
Section: Resultsmentioning
confidence: 94%
“…FSO links are of low cost, simple, and easy to install [3]. Installation is easy because no license is required from FCC for using FSO [4]. Also, there is no time and money wastage in digging the street to lay fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The two carrier waves are represented by in-phase (I) and quadrature-phase (Q) components of the signal. Here, M=8 for 8-QAM, M=16 for 16-QAM, and so on [4]. The unconditional BER for M-ary QAM is given as [2] ( ) ( )…”
Section: Mathematical Preliminaries For Bit Error Rate Calculationmentioning
confidence: 99%
“…access huge bandwidth available in optical fibre is wavelength division multiplexing (WDM) [15][16][17].…”
Section: International Journal Of Computer Applications (0975 -8887) mentioning
confidence: 99%